Prelithiation Reagents and Strategies on High Energy Lithium‐Ion Batteries - Xin, Chen; Gao, Jian; Luo, Rui; Zhou, Weidong (Chemistry : a European journal, 2022)
Lithium‐ion batteries (LIBs) have been widely employed in energy‐storage applications owing to the relatively higher energy density and longer cycling life. However, they still need further improvement especially on the energy density to satisfy the increasing demands on the market. In this respect, the irreversible capacity loss (ICL) in the initial cycle is a critical challenge due to the lithium loss during the formation of solid electrolyte interphase (SEI) layer on the anode surface. The strategy of prelithiation was then proposed to compensate for the ICL in the anode and recover the energy density. Here, various methods of the prelithiation are summarized and classified according to the basic working mechanism. Further, considering the critical importance and promising progress of prelithiation in both fundamental research and real applications, this Review article is intended to discuss the considerations involved in the selection of prelithiation reagents/strategies and the electrochemical performance in full‐cells. Moreover, insights are provided regarding the practical application prospects and the challenges that still need to be addressed. The strategy of prelithiation is an effective pathway to supply Li source for compensating the lithium loss in the first cycle, thus promoting the energy density of batteries. This review outlines the chemical and electrochemical prelithiation methods for anodes and cathodes, with particularly discussion on the complexity of different prelithiation reagents/strategies and corresponding lithiation degree reached.